Characteristics of ictal EEG in Magnetic Seizure Therapy at various stimulation frequencies. Issue 8 (August 2018) - Backhouse, Felicity A.; Noda, Yoshihiro; Knyahnytska, Yuliya; Farzan, Faranak; Downar, Jonathan; Rajji, Tarek K.; Mulsant, Benoit H.; Daskalakis, Zafiris J.; Blumberger, Daniel M.
Highlights: Magnetic Seizure Therapy (MST) stimulation frequency impacts seizure characteristics. Seizure qualities predict response differently in MST and ECT which may suggest different mechanisms. Lower slow-wave amplitude and shorter polyspike duration may predict response to MST. Abstract: Objectives: The first objective of this study aimed to elucidate the relationship between seizure characteristics and Magnetic Seizure Therapy (MST) treatment outcome. The second objective was to determine the effect of stimulation frequency on seizure characteristics. Methods: Using a between-subjects design, we compared the seizures of patients with unipolar depression receiving MST at three separate stimulation frequencies: 25 Hz ( n = 34), 50 Hz ( n = 16) and 100 Hz ( n = 11). Seizures were rated for overall seizure adequacy on a scale of 0–6, with one point given for each measure that was considered to be adequate according to the ECT literature: (1) seizure EEG duration (2) motor duration, (3) post-ictal suppression, (4) ictal EEG maximum amplitude, (5) Global Seizure Strength, and (6) Symmetry. Mixed-effect models were used to evaluate the effect of frequency on seizure characteristics and the relationships between seizure characteristics and clinical outcome. Results: (1) 100 Hz induced seizures that were less adequate than seizures induced with 50 Hz and 25 Hz stimulations. Seizures induced by 50 Hz stimulations had longer slow-wave phase durations and total EEG durations than the 100 Hz and 25 Hz groups. Global seizure strength was less robust in seizures induced by 100 Hz MST compared to the other stimulation frequencies. (2) Shorter polyspike durations and smaller slow-wave amplitude predicted reductions in overall symptoms of depression as measured by the 24-item Hamilton Depression Scale. Conclusion: Analysis of our first objective revealed stimulation frequency significantly influences measures of overall seizure adequacy. However, our results also revealed these descriptions of seizure adequacy based on ECT literature may not be useful for MST-induced seizures, as the characteristics of MST-induced seizure characteristics may predict clinical response in a different manner. Significance: These results may help to distinguish the biological processes impacted by stimulation frequency and may suggest different mechanisms of action between convulsive therapies and challenge the current understanding of seizure adequacy for MST.